(untitled) (Conferencea, 2023)
Obviously, the image of a person and their characteristics is formed according to the dominant metaphorical model HUMAN is an ANIMAL. This conceptual metaphor is verbalized by linguistic metaphors characterizing animals, forming a system for describing a person’s image in relation to the animal’s description. Accordingly, the conceptual area ANIMAL is projected onto the conceptual area HUMAN.